Religious oppression: government regulations and social hostilities - Somasundram, Sotheeswari; Siraq, Abdalla; Rasiah, Ratneswary; Habibullah, Muzafar Shah (KODISA, 2017)
Religious intolerance has become a common feature of many countries in recent times. Studies have revealed a worldwide increase in government regulations and social hostilities against religious beliefs and practices. The stifling impact of both government and society on the market for religion, warrants closer scrutiny. This study examines the relationship between government regulations and social hostilities towards religious beliefs and practices, for the period of 2001-2011 for a sample of 45 European countries. The Generalized Method of Moments dynamic panel estimation technique is employed to analyze the micro panel dataset of 45 European countries, to establish the possible relationships that may exist between these variables. The theoretical framework for this study is based on the Religious Economies Theory and the Supply Side Theory of Religion. The results of this study show evidence of the positive relationship between government regulations and social hostility. Interestingly, the study also revealed that the impact of social hostility on the level of government restrictions is smaller in magnitude compared to the reverse impact of government restrictions on social hostilities, indicating the dangerous role played by governments in inciting social hostilities, when they regulate or restrict religious beliefs and practices.